Impact of lack of transportation on access to dental care - Jaewhan Kim; Indrakshi Roy; E. Angeles Martinez-Mier; Anubhuti Shukla; Peter Weir (Heliyon)
Objectives: Access to healthcare may be influenced by the availability of transportation. Nevertheless, the impact of transportation challenges on access to dental care has not been thoroughly examined. This study investigates the influence of transportation availability on dental care visits, dental cleanings, and exams. Methods: This is a retrospective observational study. The 2021 Medical Expenditure Panel Survey (MEPS), a national survey in the United States, was used for this study. Adults (≥18 years old) from the 2021 survey were included. The 2021 Full Year Consolidated File and the Dental Visits file were linked to identify the main independent variable and the outcomes.Weighted zero-inflated negative binomial regression and weighted logistic regression were employed to analyze the outcomes of dental care visits, and dental cleanings, and exams. Results: The study included a total of 204,704,044 adults, with an average age of 49 (SD: 18) years, and a 51 % female representation. Approximately 5.5 % (n=11,285,968) of the population reported facing transportation challenges. Subjects encountering transportation challenges exhibited a 26 % decrease in dental care visits compared to those without such challenges (Incidence Rate Ratio (IRR)=0.74, p < 0.01, 95 % CI: 0.64–0.87). Individuals lacking transportation had 39 % lower odds of receiving a dental cleaning (odds ratio (OR)=0.61, p < 0.01, 95 % CI: 0.48–0.77) and 29 % lower odds of undergoing a checkup or exam (OR=0.71, p < 0.01, 95 % CI: 0.56–0.90). Conclusions: The study's findings underscore the significant impact of transportation challenges on access to dental care. Limited access to dental care due to transportation issues could exacerbate disparities in oral health outcomes. Implementing targeted interventions to address transportation challenges could contribute to improved oral health outcomes.